Construction X-Bar Chart for Quality Control Using of Robust (MAD) Estimator in Under Consideration Is Outlier with An Application - Dlshad Mahmood Saleh; Dashty Ismil Jamil (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The presence of outliers in a sample significantly affects the estimated values, which is why the highly efficient Median Absolute Deviation (MAD) method has been used due to of its great robust against the existence of outliers values in the data. In this article, we construct a mean quality control charts using the (MAD) robust. A comparison between the mean control chart based on robust and the mean control chart based on standard deviation to reach a better method, this is through a practical application to the real data (the pressure force on the block). The findings revealed that mean control chart based on (MAD) was more effective than the classical mean control chart based on standard deviation in identifying anomalies from the average production process.